The Hydroquinone Content in Whitening Cream Samples Sold Through Online Marketplace: Kandungan Hidroquinon Dalam Sampel Krim Pemutih Yang Dijual Melalui Online Shop - Nuriyah Umi Lathifatun Nuriyah; Herni Setyawati; Eviomita Rizki Amanda (Journal Pharmasci (Journal of Pharmacy and Science), 2023)
Whitening cream is a product that has an active ingredient composition that can slow down the formation of melanin so that it can whiten the skin. Hydroquinone is an active compound that is usually added to whitening cream preparations to prevent pigmentation which causes skin darkening. So that the process of use must be monitored. But the rise of cosmetic products on the market, especially online marketplaces, is an opportunity for weak supervision by drunken parties. For this reason, qualitative and quantitative analysis of hydroquinone compounds in whitening cream preparations sold on online marketplaces needs to be carried out. Qualitative analysis was carried out by testing the color reaction using FeCl3, benedict, and fluoroglucine reagents. From the qualitative analysis, 2 hydroquinone positive samples were obtained from 10 tested whitening cream samples. Quantitative analysis was carried out using the UV-Vis spectrophotometry method using fluoroglucin. The results of the analysis showed that the cream sample proved to contain hydroquinone, namely sample B with 0.073 ppm and sample F 0.044 ppm.